Magnetic properties of N‐doped multi‐walled carbon nanotubes. Issue 2 (13th March 2013) - Grechnev, G.E.; Desnenko, V.A.; Fedorchenko, A.V.; Panfilov, A.S.; Kolesnichenko, Y.A.; Khrapatiy, S.V.; Prylutskyy, Y.I.; Matzui, L.Y.; Ritter, U.; Scharff, P.
Abstract The magnetic properties of nitrogen‐doped multi‐walled carbon nanotubes (N‐MWCNTs) were studied in the temperature and magnetic field range of (4.2–290) K and (0.05–30) kOe, respectively. Also magnetic properties of the reference MWCNTs without nitrogen doping were investigated on the same footing for comparison. The presence of iron‐based particles inside N‐MWCNTs was detected. The low temperature SQUID (Superconducting Quantum Interference Device) magnetization measurements were supplemented with thermogravimetric analysis. The magnetic characterization provided the saturation magnetic moment MS and residual magnetization MR of N‐MWCNTs to be, respectively, 4.5 emu/g and 0.9 emu/g, whereas for the reference MWCNTs the corresponding parameters are found to be about twice higher. The coercive field value amounts to 800 Oe for both systems at low temperatures, then decreasing to about 450 Oe at 200 K.